Development of HTS Current Leads for the ITER Project. Issue 1 (March 2020) - Bauer, P; Ballarino, A; Devred, A; Ding, K; Dong, Y; Niu, E; Du, Q; Gung, C Y; Han, Q; Heller, R; Huang, X; Ichihara, T; et al.
Abstract: The HTS current leads for the ITER project will be the largest ever operated, with unprecedented currents, up to 68 kA and voltages, up to 14 kV. According to the ITER agreement they will be provided in-kind by China. After an extensive development program at the Hefei Institute of Plasma Physics (ASIPP), the ITER current leads were designed and qualified. The following discusses the main highlights of this development, with particular emphasis on the description of the design of the different types of ITER current leads and their final qualification in dedicated cold tests in nominal conditions.